Lower-Extremity Strength Ratios of Professional Soccer Players According to Field Position. Issue 5 (May 2015) - Ruas, Cassio V.; Minozzo, Felipe; Pinto, Matheus D.; Brown, Lee E.; Pinto, Ronei S.
Abstract : Abstract: Ruas, CV, Minozzo, F, Pinto, MD, Brown, LE, and Pinto, RS. Lower-extremity strength ratios of professional soccer players according to field position. J Strength Cond Res 29(5): 1220–1226, 2015—Previous investigators have proposed that knee strength, hamstrings to quadriceps, and side-to-side asymmetries may vary according to soccer field positions. However, different results have been found in these variables, and a generalization of this topic could lead to data misinterpretation by coaches and soccer clubs. Thus, the aim of this study was to measure knee strength and asymmetry in soccer players across different field positions. One hundred and two male professional soccer players performed maximal concentric and eccentric isokinetic knee actions on the preferred and nonpreferred legs at a velocity of 60°·s −1 . Players were divided into their field positions for analysis: goalkeepers, side backs, central backs, central defender midfielders, central attacking midfielders, and forwards. Results demonstrated that only goalkeepers (GK) differed from most other field positions on players' characteristics, and concentric peak torque across muscles. Although all players presented functional ratios of the preferred (0.79 ± 0.14) and nonpreferred (0.75 ± 0.13) legs below accepted normative values, there were no differences between positions for conventional or functional strength ratios or side-to-side asymmetry. The same comparisons were made only between field players, without inclusion of the GK, and no differences were found between positions. Therefore, the hamstrings to quadriceps and side-to-side asymmetries found here may reflect knee strength functional balance required for soccer skills performance and game demands across field positions. These results also suggest that isokinetic strength profiles should be considered differently in GK compared with other field positions due to their specific physiological and training characteristics.